Oryza sativa L. extracts inhibit nitric oxide production and inducible nitric oxide synthase expression in murine macrophage cells and lungs of antigen-challenged allergic mice - Cheol Yong Lee; Min Jung Lee; Ju Mi Kim; Seul Min Choi; Kyung Koo Kang; Ok Jin Kim; Byung Mu Lee (International Journal of Phytomedicine, 2015)
Hyper-production of nitric oxide (NO) has been observed in the airways of patients with asthma and may contribute to airway inflammatory responses. Previous studies showed that DA-9201, an ethanolic extract of Oryza sativa L., significantly attenuated airway hyperresponsiveness, airway inflammation, and remodeling in murine models of asthma. The purpose of this study was to examine the effect of DA-9201 on the expression of inducible NO synthase (iNOS) and NO production in RAW 264.7 murine macrophage cells and ovalbumin (OVA)-sensitized allergic mice. The levels of NO and iNOS expression in lipopolysaccharide (LPS)-stimulated RAW 264.7 cells were determined. Allergic inflammation was induced in mice by immunization with OVA and these mice were administered DA-9201 daily at 30, 100 or 300 mg/kg for 2 weeks. Mice were challenged with allergen by inhalation during the last 3 days of DA-9201 treatment and lungs were harvested 24 h after the last challenge. NO levels in blood plasma and iNOS expression in lung tissue were determined by ELISA and western blotting, respectively. DA-9201 inhibited the production of NO and iNOS gene and protein expression in a dose-dependent manner in LPS-stimulated cells. In the lungs of allergen-challenged mice, DA-9201 caused a significant decrease in iNOS protein expression. Furthermore, we found that DA-9201 significantly decreased NO levels in blood plasma. These results suggest that DA-9201 inhibits NO production by limiting the expression of iNOS, which may be one of the underlying mechanisms its anti-asthmatic effect.